MENARIK BENANG MERAH IMPLEMENTASI MERDEKA BELAJAR-KAMPUS MERDEKA DI UNIVERSITAS NEGERI MEDAN DAN UNIVERSITAS SYIAH KUALAH BANDA ACEH - Susilo Surahman; Muhammad Julijanto; Sulhani Hermawan (Muróbbî: Jurnal Ilmu Pendidikan, 2022)
On the one hand, independent campuses gave birth to new learning concepts and strengthened cooperation networks with parties outside the university. But on the other hand, the separate campus faces various obstacles in its implementation. This paper aims to explain the implementation of Merdeka Belajar-Kampus Merdeka (MBKM) at Medan State University and Syiah Kuala University Banda Aceh. This research is a type of field research—data collection through observation, interviews, and documentation. Data analysis is carried out descriptively by triangulation. The results showed that Medan State University and Syiah Kuala University Banda Aceh applied the same pattern: the learning block model outside higher education, the non-block learning model outside higher education, and the acceleration model. Meanwhile, the obstacle faced by these two universities is the readiness factor.